Efektivitas Tingkat Konsentrasi dan Kecemasan Terhadap Ketepatan Shooting Futsal - Andrian Prayoga; Ajeng Dewi Ramadani; Dicky Hendrawan (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2024)
This study investigates the impact of concentration on shooting accuracy in futsal. It primarily seeks to establish the connection between concentration and shooting accuracy, while also examining the influences of anxiety and experience. Employing a quantitative correlational design, the research involved a sample of 30 male high school futsal players aged 15-18 years with varying experience. Concentration was assessed via the Grid Concentration Exercise Test (GCET), and shooting accuracy was evaluated through the Shooting Accuracy Test (SAT) across three sessions. The findings indicated a strong positive correlation between concentration and shooting accuracy (β=0.65, p<0.001). Path analysis confirmed anxiety's significant mediating role (indirect effect=0.15, p=0.002), with heightened concentration levels mitigating anxiety (β=-0.42) and enhancing shooting precision. Furthermore, playing experience moderated the concentration-accuracy linkage, revealing a stronger correlation in experienced players (r=0.81) compared to novices (r=0.54). These results underscore the necessity for futsal training programs that incorporate concentration and anxiety management strategies tailored to players' experience levels.